Visualizing Walmart’s Supply Chain Management: A Case Study on Detailed Warehouse Management Practices - Zhai , Xuyuan (Transactions on Economics, Business and Management Research, 2024)
Supply chain management (SCM) plays a critical role in the success of modern businesses. Visualization techniques have become increasingly important in improving these processes. These methods have become increasingly significant in recent years, offering new ways to understand and optimize complex supply chain processes. This study focuses on how Walmart uses visualization in its supply chain management to boost efficiency and decision-making. This paper examines the integration of technologies like real-time tracking and data analysis into Walmart’s practices, discussing both the advantages and challenges they bring. Walmart has embraced visualization technologies to streamline its SCM processes and make more informed decisions. Furthermore, the paper explores how visualization can help with inventory management, demand forecasting, and logistics optimization in Walmart’s supply chain. Combined with relevant literature and case studies, it sheds light on how visualization enhances supply chain operations, offering insights for academics and industry professionals alike, that give good suggestions to the market.